Autogenous bone grafts in periodontal practice: A literature review - Nymphea Pandit; Inder Kumar Pandit (Wolters Kluwer Medknow Publications, 2016)
To improve the long-term prognosis of teeth, the treatment of periodontal diseases has evolved from resection to regeneration. Regeneration of the supporting structures of the teeth involves the use of a variety of materials of natural and synthetic origins. The ultimate aim of a true connective tissue attachment to the cementum, however, is difficult to achieve and a few of the materials have shown promising results. Autogenous bone graft obtained from the same individual has always been considered the gold standard because of its high osteogenic potential and virtually nil side effects. The present paper describes the use of autogenous grafts in the periodontal practice. The compilation of the data was done by PubMed search since the first use of the graft in periodontics.